(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: The use of labor induction to shorten the duration of a pregnancy has increased steadily during the last few decades. Paraoxonase 1 levels were observed to be higher in the oxytocin-induced group than in the spontaneous labor group. Objective: To compare the influence of induced labor on fetal Apgar score and birthweight, and to measure the level of oxidative stress (paraoxonase 1) experienced during labor by the neonates of pregnant women undergoing induced or spontaneous birth. Methods: A case control study that was conducted in the Department of Obstetrics and Gynecology, Azadi Teaching Hospital, Kirkuk during a period of nine months from 10th of February till 10th of November 2019. It included 60 healthy pregnant women with singleton pregnancy and viable fetus attending the labor room of the hospital. They were divided into two groups: Case group included 30 pregnant women who underwent oxytocin-induced labor and control group included 30 pregnant women underwent spontaneous vaginal delivery in latent phase of first stage labor without oxytocin induction. A five ml of blood was drawn from the umbilical artery to measure Paraoxonase 1 level. Pregnancy outcome was also monitored. Results: The mean of Paraoxonase 1 enzyme was significantly higher in women who underwent oxytocin-induced labor than that in women who underwent vaginal delivery without oxytocin induction. No significant differences between study groups regarding birthweight, Apgar score 1 min, Apgar score 5 min, packed cell volume, and hemoglobin F. Conclusion: Serum Paraoxonase 1 as a marker was elevated in neonates of pregnant women who underwent oxytocin induced labor without a significant effect on Apgar score of neonates or its birthweight. Keywords: Paraoxonase 1, labor induction, oxidative stress, pregnancy outcome Citation: Ahmed SN, Ghalib AK. Evaluation of paraoxonase 1 oxidative stress enzyme in cord blood of newborn to patients delivered with oxytocin induced labor. Iraqi JMS. 2022; 20(2): 168-174. doi: 10.22578/IJMS.20.2.2